Determination of Leisure Time Orientations in University Students, The Relationship Between Leisure Time Boredom Perceptions and Social Network Sites Usage Purposes - Nazlı Deniz Öz; Metin Özlü; Erdal Taşgın (Selcuk University, 2018)
The purpose of this study is to determine the leisure time preferences of the university students and to examine the relationship between leisure time perception and usage of social network sitesThe research was conducted in accordance with the relational screening model. The study group consists of 230 female (65.7%), 120 male (34.3%), total 350 students studying at Konya Selçuk University. As a means of data collection in the study that personal information form, activity preference form and "Social Network Sites Usage Scale" developed by Karal and Kokoç (2010) and "Leisure Time Boredom Perception Scale" (LTBPS) developed by Iso-Ahola and Weissinger and adapted to Turkish by Kara et al. (2014) was used. SPSS 16.0 statistical package program was used to evaluate the data and to find the calculated values. The data are summarized by giving percent, mean and standard deviations. Independent group t test was used for binary cluster comparisons and One Way Variance Analysis (ANOVA) was used for multiple cluster comparisons due to the data showed normal distribution. Significance level in the study was taken as (p lt;0.05). As a result of the study, in favour of male participants in the sub-dimension of boredom from LTBPS sub-dimensions according to gender variable, in favour of male participants in all SNSUPS sub-dimensions; for 1-3 hours according to the weekly leisure time variable in the case of two of the LTBPS sub-dimensions, and SNSUPS sub-dimensions for 1-3 hours and 4-6 hours in sub-dimension for identification and recognition; there was no significant difference in the LTBPS sub-dimension according to the activity preference variable, but significant results were observed in all SNSUPS sub-dimension. According to the relationship test between SNSUPS and LTBPS, low and moderate positive correlations were found in all sub-dimensions of the two dimensions.